2000
DOI: 10.1111/j.1749-6632.2000.tb05612.x
|View full text |Cite
|
Sign up to set email alerts
|

A Caspase‐Independent Cell Clearance Program: The LEI/L‐DNase II Pathway

Abstract: The discovery of caspase‐mitochondrial pathway counts as one of the most important discovery in apoptosis biochemistry. Today, however, we begin to recognize its limits. Inhibition of caspase does not prevent cell death in many mammalian models. Targeted disruption of caspases does not impair every type of apoptosis. Other pathways, caspase independent, are now described. Here we present one of these pathways. It is a serine‐protease dependent pathway and its key event is the transformation of LEI (a serine pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 58 publications
0
12
0
Order By: Relevance
“…The mechanism that leads to the activation of L-DNase II involves LEI cleavage by specific enzymes. Previous studies have shown that elastase-like molecules activate this enzyme under certain conditions [6]. In the retina, recent works have indicated that elastase is not required for L-DNase II activation during apoptosis in developing neural retina in the chick, where an acid protease seems to be responsible for LEI cleavage [18].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The mechanism that leads to the activation of L-DNase II involves LEI cleavage by specific enzymes. Previous studies have shown that elastase-like molecules activate this enzyme under certain conditions [6]. In the retina, recent works have indicated that elastase is not required for L-DNase II activation during apoptosis in developing neural retina in the chick, where an acid protease seems to be responsible for LEI cleavage [18].…”
Section: Resultsmentioning
confidence: 99%
“…Different caspase-independent pathways have been described [3,6]. Several proteases have been involved in caspase-independent apoptosis: calpains, cysteine cathepsins B and L, aspartate cathepsins D and various serine proteases (Granzymes A and B, Omi/HtrA2, AP24) [3,6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…LEI is a serine protease inhibitor that regulates the activity of neutrophil elastase, cathepsin G, and proteinase-3. In addition, it has been suggested that, after cleavage of its reactive group, it is transformed into a DNase that may digest nuclear DNA during apoptosis (37). Interestingly, a potential role for inhibitors of neutrophil elastase has been proposed for the treatment of inflammatory diseases in the airways (see Ref.…”
Section: Resultsmentioning
confidence: 99%
“…Caspase proteases are executors of apoptotic cell death. Caspase activation regulates endonuclease activation, resulting in cleavage of internucleosomal DNA and cell death (32,50). Although apoptosis is a normal aspect of enterocyte turnover and renewal, accelerated apoptosis can lead to a breach in the intestinal mucosal barrier.…”
Section: Discussionmentioning
confidence: 99%